-4=-8y+2(y+4)

Simple and best practice solution for -4=-8y+2(y+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4=-8y+2(y+4) equation:


Simplifying
-4 = -8y + 2(y + 4)

Reorder the terms:
-4 = -8y + 2(4 + y)
-4 = -8y + (4 * 2 + y * 2)
-4 = -8y + (8 + 2y)

Reorder the terms:
-4 = 8 + -8y + 2y

Combine like terms: -8y + 2y = -6y
-4 = 8 + -6y

Solving
-4 = 8 + -6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '6y' to each side of the equation.
-4 + 6y = 8 + -6y + 6y

Combine like terms: -6y + 6y = 0
-4 + 6y = 8 + 0
-4 + 6y = 8

Add '4' to each side of the equation.
-4 + 4 + 6y = 8 + 4

Combine like terms: -4 + 4 = 0
0 + 6y = 8 + 4
6y = 8 + 4

Combine like terms: 8 + 4 = 12
6y = 12

Divide each side by '6'.
y = 2

Simplifying
y = 2

See similar equations:

| -2+8s^2+3s^4=0 | | -2u+4(u-2)=-4 | | 4x(x+2)+11-4=2x+3 | | 12s^4+32s^2-8=0 | | 5(x-5)-6x=-2 | | 7/12*9/2-33/40 | | (2x^2-6x-8)/(x+1) | | 3s^4+8s^2-2=0 | | 7/x+3-5/x-3=3x/x^2-9 | | 14x^2/7x | | -13+6=m-10 | | 6v^2+3v-4=-4v^2 | | 3a^2-14a-5=0 | | 2v^2+3v-4=0 | | -13+6=m-16 | | y=-1*1 | | 7/12x9/2-33/40 | | 4/5b=120 | | 4/5b=48 | | y=-3/4*1+6 | | -0.75*-3/4x+6 | | x^2+5x-37.5=0 | | 96x^2-204x-99=0 | | 450+0.06s=0.06s+900 | | x-43=0 | | 3(6s+12)-10s-6=0 | | 6*4-4y=-24 | | 15c^2-17c-42=0 | | 6x-4*4=-24 | | x^2-x-169=0 | | 13x+10y=20 | | 44x+7=x |

Equations solver categories